Solon of Athens : Poet, Philosopher, Soldier, Statesman. - Owens, Ron (Liverpool University Press, 2010)
Addresses the historical, social and political contexts within which Solon of Athens instituted wide-ranging reforms to the Athenian constitution (594-93 BCE), the impact of those reforms on the political self-awareness of the archaic Athenians themselves, and the ethical and political philosophies that drove reform.
Description based upon print version of record.
Keywords: Solon, -- approximately 630 B.C.-approximately 560 B.C.; Statesmen -- Greece -- Biography.; Poets, Greek -- Biography.; Philosophers -- Greece -- Biography.; Athens (Greece) -- Politics and government.; Hommes d'État -- Grèce -- Biographies.; Poètes grecs -- Biographies.; Philosophes -- Grèce -- Biographies.; HISTORY / Ancient / Greece